2022
DOI: 10.1590/acb370602
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of colitis by oral negatively charged nanostructured curcumin in rats

Abstract: Purpose: To examine the effects of a negatively charged nanostructured curcumin microemulsion in experimental ulcerative colitis (UC) in rats. Methods: Four percent acetic acid was used to induce UC. The animals were treated for seven days and randomly assigned to four groups: normal control (NC), colitis/normal saline (COL/NS), colitis/curcumin (COL/CUR), and colitis/mesalazine (COL/MES). The nanostructured curcumin was formulated with a negative zeta potential (-16.70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In this scenario, we find curcumin, a polyphenol isolated from the rhizome of Curcuma longa L. [ 8 ]. Its chemical structure consists of two aromatic rings containing hydroxyl and methoxy groups, which are linked through a chain containing seven carbons of an α,β-unsaturated β-diketone moiety [ 26 , 27 ].…”
Section: Curcumin and Its Anticancer Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, we find curcumin, a polyphenol isolated from the rhizome of Curcuma longa L. [ 8 ]. Its chemical structure consists of two aromatic rings containing hydroxyl and methoxy groups, which are linked through a chain containing seven carbons of an α,β-unsaturated β-diketone moiety [ 26 , 27 ].…”
Section: Curcumin and Its Anticancer Effectsmentioning
confidence: 99%
“…In this context, curcumin emerges as a potential bioactive with extensive anticancer potential against different types of cancer [ 7 ]. Curcumin is a major natural compound obtained from the rhizome of Curcuma longa L. [ 8 ]. Despite its high biological potential, it has biopharmaceutical limitations that compromise its clinical use in cancer therapy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its good tolerance profile and safety even at high doses (12 g/day), curc has been extensively studied as a therapeutic agent [11,14]. Numerous preclinical and clinical trials have concluded that curc has great potential for the treatment of various diseases in humans [37][38][39].…”
Section: Curcumin and Its Antileishmanial Propertiesmentioning
confidence: 99%